SIMULATION OF SO2 DISPERSION USING FLUENT MODEL AND DOUBLE GAUSS DIFUSSION MODEL (Case Study at PLTU PT. INDORAMA SYNTHETICS ltd.) - SETIO PRASANTO (NIM 12802014), BUDI
Based on concept of fluids mechanical plume emission of sulfur dioxide which is released to atmosphere and its form of fluid flow and can changes continuously. Every substance of chemical that releases to atmosphere, will be transported, diffused and dispersed with dynamical fluid process. At present, there is many simulation tool that has been developed for simulation of gas dispersion or substance dismissal that is released to the atmosphere, and Computational Fluent Dynamic (CFD) or Fluent model is one of them. Fluent model approach has been taken, by solving steady-state, with conservation mass and momentum of Reynolds-Averaged Navier-Stokes (RANS). Turbulence modeling is based upon the standard k-e model. And calculation of diffusion flux based on chemical species transport that contain in Fluent. Beside it, in this research also use a Gauss diffusion model to compare the results from Fluent model. On Gauss diffusion model, calculation of diffusion flux use equation that has been developed by Pasquill-Grifford. By used a measured meteorological and field sampling data from 31st of October 2003 at PLTU PT. Indorama Synthetic ltd. that located in Jatiluhur, Purwakarta for the simulation. The results of Fluent model provide higher in accuracy toward sampling data, with 66.3 % than double Gauss diffusion model that provide 2.6% toward sampling data.